School Readiness of Early Childhood Age 5-6 Years Based on The Nijmeegse Schoolbekwaamheid Test (NST) - Fajariyah, Puja Nor (Jurnal Penelitian Anak Usia Dini, 2022)
School readiness is the achievement of children’s maturity in aspect of development which include physical and motor development, social emotional development, cognitive development, language and communication development, and motivation and work attitude so that they can continue their education to the elementary school level. This study aimed to know the school readiness of early childhood age 5-6 years based on the Nijmeegse Schoolbekwaamheid Test (NST). This study uses quantitative research using a survey method with a target of number 43 early childhood age 5-6 years from 3 different kindergartens of Malang. The instrument using in this study is the Nijmeegse Schoolbekwaamheid Test (NST) which the result test is divided into 3 stages of school readiness called mature, hesitant, and immature. The findings from this study are that early childhood age 5-6 years in Malang kindergartens have school readiness to continue to elementary school level based in the results of the the Nijmeegse Schoolbekwaamheid Test (NST).